Application of bioethics in innovation and quality testing of chili seeds (Capsicum annum L.) at the Horticulture UPT - Nurbaity Situmorang; Mery Christianna Larrisa Sinaga; Syalsabila Pane (EduMatika: Jurnal MIPA, 2026)
Red chili (Capsicum annuum L.) is a horticultural commodity with high economic value in Indonesia, but its productivity has not yet reached its optimal potential. One important factor in increasing productivity is the use of quality seeds with high viability and vigor. This study aims to evaluate the role of chili seed innovation through a critical thinking approach and the application of bioethical principles in horticultural development at the Medan Horticultural Seed Development Unit (UPT). This study emphasizes the importance of applying the principles of benefit, non-maleficence, autonomy, and justice in the process of testing seed moisture content and germination. The results of the study indicate that seed innovation accompanied by the application of bioethics can improve seed quality while maintaining moral responsibility towards farmers, consumers, and the environment. Thus, chili seed development based on bioethics is an important strategy in realizing sustainable and competitive horticulture.